The Effect of Physical Activity at Home on Reducing Stress and Anxiety Levels in Remote Workers - Irman P, Dede; Surya P, Dhika (International Journal of Health, Medicine, and Sports, 2024)
In the era of remote work, workers often experience mental challenges due to social isolation and difficulty separating work time from personal time, which can increase the risk of stress and anxiety. Physical activity is believed to have a positive effect on mental health, but most studies have focused on activities outside the home, such as exercising at the gym or group activities. This study aims to fill this gap by examining the effect of frequency and duration of physical activity at home on stress and anxiety in remote workers. A total of 180 remote workers from various professions participated in this survey, where data were collected using the Perceived Stress Scale (PSS) and Generalized Anxiety Disorder Scale (GAD-7), as well as a physical activity questionnaire. The analysis was carried out using Pearson correlation tests and multiple linear regression. The results showed that the frequency and duration of physical activity at home had a significant negative relationship with stress and anxiety scores, where a one-day increase in physical activity frequency was associated with a decrease in stress and anxiety scores. The coefficient of determination (R²) showed that the frequency and duration of activity together explained about 20% of the variation in stress and anxiety scores. These findings suggest that physical activity at home may be an effective strategy for managing stress and anxiety in remote workers, and provide practical implications for companies looking to support their employees’ mental health in a remote work context.